Antioxidant Activity Assay of Dragon Fruit Extract (Hylocereus undatus (Haw.) Britt. & Rose - Evi Umayah U; Moch Amrun H (Jurnal ILMU DASAR, 2007)
Dragon fruit (Hylocereus undatus (Haw.) Britt. & Rose) familia Cactaceae has been cultivated for its beneficial properties on lowering both blood’s cholesterol and glucose level which were related with free radical-antioxidant mechanism. The fruits content antioxidants compound such as vitamin C, caroten, betacyanin pigments dan phenol; therefore it is necessary to determine its antioxidant activity. In this study, the antioxidant activity was performed on both methanolic and water extracts of dragon fruit (planted in Rembangan-Jember area) using diphenyl picryl hydrazil hydrate (DPPH) as stable free radical in spectrophotometric methods. The result showed that both methanolic and water extract exhibits DPPH free radical scavenger as an antioxidant activity with EC50 value sequentially 1.08 % and 2.98 %.Keywords : dragon fruit, Hylocereus undatus (Haw.) Britt. & Rose, free radical, DPPH, EC50.